Analisis Tingkat Perubahan Vegetasi Hutan Mangrove Terhadap Tingkat Salinitas Menggunakan Citra Landsat - Rafly Rizqyta Ramadhan; Winardi Tjahyo Baskoro; Kadek Sumaja; Komang Ngurah Suarbawa; Putu Tedy Indrayana; Ni Nyoman Ratini (Universitas Hamzanwadi, 2024)
Research on the analysis of the level of changes of mangrove forest vegetation on the level of seawater salinity has been conducted with remote sensing methods by using Landsat 8 imagery in Tahura Ngurah Rai. The data used in this research is secondary data from the official website of the USGS (United States Geological Survey). This study aims to determine the levels of changes in mangrove forest vegetation cover in Tahura Ngurah Rai and to determine how much influence the level of mangrove forest vegetation cover has on the level of salinity in Tahura Ngurah Rai. The vegetation values were obtained by processing the NDVI index data and the salinity values were obtained by processing the SI, NDSI and VSSI index. from the results of the analysis that has been conducted, vegetation cover greatly influences the NDSI index with an increase in the total NDVI value of 25,48% and a decrease in the total NDSI value of -25,48%, with a correlation coefficient and determination of NDVI-NDSI 0.998 and 0.996 respectively.